THE PURPOSE OF ECOTOURISM IS TO ENSURE THE ENVIRONMENTAL SECURITY AND SUSTAINABLE DEVELOPMENT OF PRESENT AND FUTURE GENERATIONS (International journal of artificial intelligence, 2024)
This article analyzes regional problems in the development of tourism in the Khorezm region.